Is low molecular weight hyaluronan an early indicator of disease in avian systemic sclerosis?. (2nd September 2016) - Kerje, Susanne; Hellman, Urban; Do, Lan; Larsson, Göran; Kämpe, Olle; Engström-Laurent, Anna; Lindqvist, Ulla
ABSTRACT: Aim of the study : To further elucidate the pathogenesis of systemic sclerosis (SSc) an experimental avian model was used. The University of California at Davis line 200 (UCD-200) chickens spontaneously develop a SSc-like disease that has most features of human SSc with vascular effects, inflammation, autoimmunity, and fibrosis. The first signs of disease in UCD-200 chickens are swelling and ischemic lesions of the comb and the presence of a tissue containing high amounts of glycosaminoglycan hyaluronan (HA). The aim of this study was to evaluate inflammatory and fibrotic processes of the disease with regard to the molecular weight of HA. Material and methods : Comb biopsies from UCD-200 and healthy White Leghorn (WL) chickens, as controls, at different ages were studied with the histochemical localization of HA, hyaluronidase-1 (Hyal-1), cluster of differentiation 3, immunoglobulin Y, and collagen I and III. The molecular weight distribution of HA was estimated with gas-phase electrophoretic analysis. Results : At 2 days of age, HA was visualized in UCD-200 chickens at the dermal part of the comb with no simultaneous staining of Hyal-1. In adult UCD-200 chickens, the comb skin was almost totally devoid of HA compared to WL chickens of the same age. An increase of low molecular weight (LMW) HA was detected in comb tissue from UCD-200 at the age of 1 day, 1 week, 2 weeks, and 4 weeks, in contrast to adult animals. Conclusions : An early inflammatory process involving LMW HA was confirmed as a possible profibrotic process. This indicates that HA might be an important participant in the early inflammatory events of SSc in UCD-200 chickens and that the disappearance of HA in skin predisposes to fibrosis.